2013
DOI: 10.1364/ao.52.002353
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of utilizing Cherenkov Telescope Array gamma-ray telescopes as free-space optical communication ground stations

Abstract: The signals that will be received on Earth from deep-space probes in future implementations of free-space optical communication will be extremely weak, and new ground stations will have to be developed in order to support these links. This paper addresses the feasibility of using the technology developed in the gamma-ray telescopes that will make up the Cherenkov Telescope Array (CTA) observatory in the implementation of a new kind of ground station. Among the main advantages that these telescopes provide are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…This is one of the reasons to study the use of other kind of telescopes. This paper completes an initial proposal from the authors about the use of IACTs (Imaging Atmospheric Cherenkov Telescopes) as optical ground terminals in deep-space FSOC [2].…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…This is one of the reasons to study the use of other kind of telescopes. This paper completes an initial proposal from the authors about the use of IACTs (Imaging Atmospheric Cherenkov Telescopes) as optical ground terminals in deep-space FSOC [2].…”
Section: Introductionmentioning
confidence: 61%
“…The authors of this paper presented the original idea of using IACT telescopes for deep-space FSOC in a previous paper [2]. The motivations were explored back then: the big apertures of the telescopes, their native operation as an array, their low costs due to their relaxed requirements, the ideal sky-related conditions, the fast tracking of the telescopes, a suitable communications network infrastructure, etc.…”
Section: Problem and Solution Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, it will mainly be devoted to its primary task of observing Cherenkov light in air; however several other applications have been envisioned, to be preferably carried out during nights with bright moonlight which -owing to the faintness of the Cherenkov light flashes -might preclude their efficient observation. Besides intensity interferometry (Dravins et al, 2013), additional uses that have been suggested include searches for rapid astrophysical events (Deil et al, 2009;Hinton et al, 2006;Lacki, 2011), observations of stellar occultations by distant Kuiper-belt objects (Lacki, 2014), or as a terrestrial ground station for optical communication with distant spacecraft (Carrasco-Casado et al, 2013). For practical operations, one proposed concept is to place auxiliary detectors on the outside of the Cherenkov camera cover lid, an approach already realized on some telescopes (Deil et al, 2009;Hinton et al, 2006), and one that should not interfere with regular Cherenkov camera operations.…”
Section: Principles Of Intensity Interferometrymentioning
confidence: 99%